2014
DOI: 10.17219/acem/37235
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Manifestations in Patients with Ectodermal Dysplasia Syndromes

Abstract: Background. Ectodermal dysplasia (ED) is a disorder that results from abnormal formation of at least two of the four major ectodermal derivatives in the developing embryo. The ectoderm of the embryo forms the skin, teeth, hair and nails, sweat glands and part of the eyes. Objectives. The aim of this article is to reveal ophthalmologic symptoms and signs as multidisciplinary, reliable criteria for ectodermal dysplasia. Material and Methods. In this retrospective study, 24 patients with ED were analyzed from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
0
18
0
2
Order By: Relevance
“…Hairless dogs such as the Chinese crested breed demonstrate a hairless phenotype that is classified as a form of ectodermal dysplasia (ED) . Ectodermal dysplasia is a group of genetic disorders that involves a primary defect in at least two ectodermal derivatives including the skin, apocrine glands, and parts of the eyes . Corneal and conjunctival epithelial cells as well the lacrimal gland originate from the surface ectoderm .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hairless dogs such as the Chinese crested breed demonstrate a hairless phenotype that is classified as a form of ectodermal dysplasia (ED) . Ectodermal dysplasia is a group of genetic disorders that involves a primary defect in at least two ectodermal derivatives including the skin, apocrine glands, and parts of the eyes . Corneal and conjunctival epithelial cells as well the lacrimal gland originate from the surface ectoderm .…”
Section: Introductionmentioning
confidence: 99%
“…Corneal and conjunctival epithelial cells as well the lacrimal gland originate from the surface ectoderm . A human study reported that in patients with ED, ocular complaints particularly dry eye symptoms were observed . X‐linked hypohidrotic ectodermal dysplasia (EDA) is the most frequent form of EDA, and the lack of sebaceous glands have been reported in both German shepherds and humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Ophthalmic complications vary and can affect the eyelids, lacrimal system, and corneal surface and include complete limbal stem cell deficiency. 3,4 Herein we describe a case of a 73-year-old, white, female patient with an ectodermal dysplasia syndrome with typical skin, hair, and nail features in addition to a cleft palate, ankyloblepharon, and ear canal malformations. Her ocular history was significant for complete limbal stem cell deficiency, eyelid and lacrimal system abnormalities, and progressive opacification of both corneas.…”
mentioning
confidence: 99%